Electrical effects in suspended particles in a fluid - De La Cruz Ricardez, Abel (JOURNAL OF BASIC SCIENCES, 2016)
In the present contribution we analyze the effects of interaction between pure copper nanoparticles and human cells (erythrocytes) in an aqueous medium (distilled water), in qualitative form.